2019
DOI: 10.1093/jme/tjz228
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Tick Load Among Bird Body Parts: Implications for Studying the Role of Birds in the Ecology and Epidemiology of Tick-Borne Diseases

Abstract: Wild birds play important roles in the maintenance and dispersal of tick populations and tick-borne pathogens, yet in field studies of tick-borne disease ecology and epidemiology there is limited standardization of how birds are searched for ticks. We conducted a qualitative literature review of 100 field studies where birds were searched for ticks to characterize which parts of a bird’s anatomy are typically sampled. To increase understanding of potential biases associated with different sampling approaches, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Focusing on non-migrants, we found a much higher overall infestation percentage of 24.2%, suggesting birds may be more important for localized movement of ticks than previously thought, even in urban areas. Further support for this conclusion is provided by a complementary study that included extensive tick collection at the same 16 sites using carbon dioxide traps and tick flags (Roselli 2019). Using flagging and trapping, that study did not find A. maculatum at one highly urbanized site; however, we sampled one A. maculatum from a bird captured at that site.…”
Section: Importance Of Resident Birds As Carriers Of Ticks In Urban A...mentioning
confidence: 84%
See 1 more Smart Citation
“…Focusing on non-migrants, we found a much higher overall infestation percentage of 24.2%, suggesting birds may be more important for localized movement of ticks than previously thought, even in urban areas. Further support for this conclusion is provided by a complementary study that included extensive tick collection at the same 16 sites using carbon dioxide traps and tick flags (Roselli 2019). Using flagging and trapping, that study did not find A. maculatum at one highly urbanized site; however, we sampled one A. maculatum from a bird captured at that site.…”
Section: Importance Of Resident Birds As Carriers Of Ticks In Urban A...mentioning
confidence: 84%
“…We found that in Oklahoma City, birds were parasitized by A. maculatum, H. leporispalustris, and most commonly, A. americanum. The greater frequency of parasitism by A. americanum could result from the aggressive feeding habits of this species, which may enhance its hostpreference for ground-foraging birds (Goddard and Varela-Stokes 2009), or is related to how abundant this tick is in our study area (Roselli 2019). H. leporispalustris, the least commonly observed tick, was found only on four species that all forage on or near the ground: American Robin, Brown Thrasher, Carolina Wren, and Northern Cardinal.…”
Section: Importance Of Resident Birds As Carriers Of Ticks In Urban A...mentioning
confidence: 86%
“…During the examination of the bird, in order to avoid possible escapes from hand, the widely used ringer's grip or the photographer's grip is recommended (De Beer et al, 2001). It was shown that the body part of the tick infestation, may vary among tick species, while some ticks may be found on different parts of the body other than the head (Roselli et al, 2020). If time permits, the bird's whole body should be examined for ticks.…”
Section: Collection and Identification Of Ticksmentioning
confidence: 99%
“…Wild birds are an important reservoir of several tickborne viral and bacterial agents such as Anaplasma phagocytophilum, Borrelia spp., Coxiella burnetii, Rickettsia spp., and Crimean-Congo hemorrhagic fever virus (Dubska et al, 2009;Ogrzewalska et al, 2009;Elfving et al, 2010;Luz et al, 2012;Keskin et al, 2014;Leblebicioglu et al, 2014;Horak et al, 2018). Migratory birds, play a major role in the transportation of ticks to short or long distances (Hoogstraal et al, 1961;Dietrich et al, 2011;Wallménius et al, 2014), allowing ticks to establish in new areas, though resident birds can also contribute to the dispersion of ticks and tick-borne pathogens (Schneider et al, 2015;Roselli et al, 2020). To understand the eco-epidemiology of various diseases, it is important to study the interactions between ticks, their hosts, pathogens, and their biotic and abiotic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Tortoises are terrestrial reptiles that live in grassy habitats and therefore they are more likely to be infested by Hyalomma tick genus, which they move and actively chase for the host. Although many tick-borne pathogens in small mammals and birds have been well studied ( Krawczyk et al, 2020 ; Roselli et al, 2020 ), the potential of reptiles as reservoirs of zoonotic infectious agents has often been neglected ( Široký et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%